Comparing Time Series from Experiments with and without Spiralling - Anja M. Busse; Winfried Theis (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2004)
In this paper we compare data from BTA deep-hole drilling experiments conducted according to an experimental design, which had to be repeated due to the development of spiralling in all experiments in the first repetition. We compare the time series of the drilling torque and the bending moment with respect to the development of the maximal Lyapunov-Exponent and the overall relevant frequencies and the relevant frequencies on sections of the process.
Keywords: 519; Zeitreihenanalyse; Experiment; Vergleich; Theorie